Efektivitas Pembiayaan dalam Pemberdayaan Usaha Mikro pada KSPSS Al-Anshari Bukittinggi - Ivana Ivana; Amsah Hendri Doni (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
The purpose of this research is to know and analyse the effectiveness of financing in micro business empowerment at Kspps AL-Anshari Bukittinggi. This research uses a qualitative descriptive approach, namely collecting data according to what is actually then compiled, processed, analysed to be able to provide an overview of the existing problems. The author obtained information and data from informants by using interviews with informants. The results of this research explain that the effectiveness of financing in the empowerment of micro businesses at Kspps AL-Anshari Bukittinggi, namely in an effort to empower micro businesses, Kspss Al- Anshari Bukittinggi provides business capital financing to customers who apply for a pinjama for mikto business capital, so that with the financing, the customer's income as a micro business entrepreneur can be said to be effective, because every customer who is studied, the average customer's income increases. The effectiveness of financing in micro business empowerment at Kspss Al-Anshari Bukittinggi for the last five years, namely in 2018-2022. In 2018 the effectiveness ratio rate is 77% (quite effective), in 2019 the effectiveness ratio is 83% (quite effective) and in 2022 the effectiveness ratio rate is 72% (quite effective) which is included in the criteria is quite effective. This is because the realisation achieved is still far enough to differ to meet the set target. In 2020, the effectiveness level is 104% (highly effective) due to the realisation that has reached the set target. In 2021 the effectiveness level of 32% (not effective) is the lowest effectiveness level, this is realised very much different from the target. From the results of the last five years from 2018-2022 it is said to be quite effective.